Caring men and masculinities on the Balkan semiperiphery - Blagojević, Marina (Teorija in praksa, 2019)
The paper's theoretical framework is situated at the intersection of critical studies on men and masculinities with the theory of semiperipheriality. It analyses major trends in the transformation of gender regimes, including fatherhood, from the end of the 1980s until today. The analysis shows there is no simple unilinear development in the trend of men's growing engagement in caring. Instead, the emancipatory effects of care are becoming quite ambiguous for both genders since progressive social change has been taken over by a process of de-development of the semiperiphery within the larger landscape of neoliberal globalisation. To capture the change, the author introduces the novel concept of male hegemony built on opportune hybridity.
Keywords: Balkan; Fatherhood; Hegemony; Masculinity; Men; Moški; Moškost; Nadvlada; Očetovstvo; semiperiferija; skrbstveno delo